INFRARED SPECTROSCOPY AS A TOOL FOR ENHANCING THE RELIABILITY OF INTELLIGENT ANALYSIS OF SULFUR-CONTAINING COMPOUNDS IN PETROLEUM FUELS - SHTUTS, ANDRII; SAFTIUK, YAROSLAV (Herald of Khmelnytskyi National University. Technical sciences, 2025)
This paper examines the use of infrared spectroscopy as a modern and intelligent tool for determining sulfur-containing compounds in petroleum fuels. The relevance of this problem is emphasized, since excess sulfur in fuel leads to the formation of sulfur oxides that cause corrosion of engine components, shorten service life, and increase environmental impact. The analysis of the motor fuel market shows that some samples exceed DSTU 7687:2015, DSTU 7688:2015, and Euro-5 sulfur standards, confirming the need for fast and reliable express control methods. Particular attention is paid to the mid-infrared range (4000–400 cm⁻¹), where fundamental vibrational bands of S–H, C–S, S=O, SO₂, and S–S bonds are observed. These spectral features serve as a basis for determining sulfur content. A schematic optical analyzer is proposed, consisting of a radiation source, optical filters, a cuvette, and detectors. The obtained dependencies between cell thickness, optical density, and transmittance confirm the linear nature of the Beer–Lambert–Bouguer law, which underlies quantitative optical analysis. The study substantiates the use of chemometric approaches, particularly multilinear regression, for creating calibration and prediction models. The combination of IR spectroscopy with mathematical tools significantly improves accuracy and reproducibility, enabling rapid analysis without complex sample preparation. It is concluded that infrared spectroscopy is a promising method for intelligent express analysis of gasoline and diesel fuels, ensuring high measurement reliability and environmental compliance. Further development involves enhancing calibration models, minimizing measurement errors, and introducing portable IR analyzers for on-site industrial applications.